Determination of residual stresses in Ti/CFRP laminates after preparation using multiple methods. (15th February 2019) - Xu, Yingmei; Li, Huaguan; Yang, Yinfei; Hu, Yubing; Tao, Jie
Abstract: Since residual stresses significantly affect the properties of Ti/CFRP (Carbon Fiber Reinforced Polyimide) laminates, which are inevitably produced in the laminates after preparation owing to the different thermal expansion coefficients of the constituents, a finite element model was built in this work to simulate the residual stresses of Ti/CFRP laminates in the cooling process from glass-transition temperature ( T g) to ambient temperature. Distributions of stresses in each ply and interlaminar stresses between the adjacent layers were obtained. Moreover, the free boundary problem, usually leading to the generation of cracks, was observed especially at the edges perpendicular to the fiber direction. Additionally, an analytical approach and two experimental methods (layer removal method and X-ray diffraction technique) were applied to determine the residual stresses. Comparing these results, it was shown that these methods verified each other. The established model and corresponding simulation in our work were effective to describe residual stresses in Ti/CFRP laminates.